Polyphenols : prevention and treatment of human disease. - Watson, Ronald R. (Ronald Ross); Preedy, Victor R.; Zibadi, Sherma (Academic Press, 2018)
Polyphenols in Prevention and Treatment of Human Disease, Second Edition authoritatively covers evidence of the powerful health benefits of polyphenols, touching on cardiovascular disease, cancer, obesity, diabetes and osteoporosis. This collection represents the contributions of an international group of experts in polyphenol research who share their expertise in endocrinology, public health, cardiology, pharmacology, agriculture and veterinary science. Researchers from diverse backgrounds will gain insight into how clinical observations and practices can feed back into the research cycle, thus allowing them to develop more targeted insights into the mechanisms of disease. This reference fills a void in research where nutritionists and alternative therapies may be applicable.